Crosslinked Polyvinylnorbornene‐Based Membranes as a New Class of Solvent‐Resistant Nanofiltration Membranes. Issue 14 (20th June 2019) - Dujardin, Wouter; Van Goethem, Cédric; Steele, Julian A.; Roeffaers, Maarten; Vankelecom, Ivo F. J.; Koeckelberghs, Guy
ABSTRACT: Solvent resistant nanofiltration (SRNF) has received increasing attention since the turn of the century within energy‐ and waste‐efficient unit processes. This work explores the synthesis and characterization of crosslinked polynorbornenes for SRNF. A series of polyvinylnorbornene thin‐film composite membranes with increasing degree of crosslinking were prepared and tested for their SRNF performance in heptane, chloroform, and toluene. Sudan Black B (457 g mol −1 ) was used as the solute. Then, 99% retention was achieved in heptane, 86% in chloroform, and 75% in toluene. It was further shown that the permeance and retention can be fine‐tuned in these solvents by controlling the extent of crosslinking. This work thus introduces the crosslinking of polynorbornenes as a promising material route for SRNF. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1593–1600 Abstract : Polyvinylnorbornene (pVNB) is proposed as a new suitable material for the filtration of solutes from harsh organic solvents. 5‐Vinyl‐2‐nobornene is polymerized and the resulting pVNB is used in a series of membranes which are crosslinked using varying amounts of photoinitiator. Solvent resistant nanofiltration performance is measured using Sudan Black B as the solute (456 Da) and chloroform, toluene, and heptane as solvents.